Between Continuity and Change: The Legal Status of Arctic Indigenous Peoples - Mazza, Mauro (Polar Research and Policy Initiative (PRPI), 2025)
The paper analyses the Swedish national legal system for the protection and promotion of Arctic Indigenous Peoples, comparing it with the national legal systems of other Nordic countries